2021
DOI: 10.3390/metabo11070413
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Glycolytic Activity with Hyperpolarized [2H7, U-13C6] D-Glucose in the Naive Mouse Brain under Different Anesthetic Conditions

Abstract: Glucose is the primary fuel for the brain; its metabolism is linked with cerebral function. Different magnetic resonance spectroscopy (MRS) techniques are available to assess glucose metabolism, providing complementary information. Our first aim was to investigate the difference between hyperpolarized 13C-glucose MRS and non-hyperpolarized 2H-glucose MRS to interrogate cerebral glycolysis. Isoflurane anesthesia is commonly employed in preclinical MRS, but it affects cerebral hemodynamics and functional connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Certainly, robust protocols for imaging unanesthetized animals would be a large step toward improving comparability. In the meantime, obtaining data under multiple contrasting anesthetic conditions ( Williams et al, 2010 ; Flatt et al, 2021 ; Mathew et al, 2021 ; Stenroos et al, 2021 ) can help to identify features that are anesthesia-specific and less likely to be conserved in awake animals, and common features that are more likely to be conserved. The use of awake animals also opens the door for some specific behavior-related brain activity studies, in addition to a common sensory stimulation study paradigm.…”
Section: Open Questions and Challengesmentioning
confidence: 99%
“…Certainly, robust protocols for imaging unanesthetized animals would be a large step toward improving comparability. In the meantime, obtaining data under multiple contrasting anesthetic conditions ( Williams et al, 2010 ; Flatt et al, 2021 ; Mathew et al, 2021 ; Stenroos et al, 2021 ) can help to identify features that are anesthesia-specific and less likely to be conserved in awake animals, and common features that are more likely to be conserved. The use of awake animals also opens the door for some specific behavior-related brain activity studies, in addition to a common sensory stimulation study paradigm.…”
Section: Open Questions and Challengesmentioning
confidence: 99%
“…As substrate transport across the BBB is the rate-limiting step in brain pyruvate metabolism, higher conversion is indeed more likely "in diseases in which the blood brain barrier is expected to be focally disrupted", as posed by Miller et al 19 Additionally, it has been shown in multiple studies that the level and type of anesthesia and carrier gas affect the metabolic conversion in HP 13 C MRI/MRS. 4,[45][46][47][48] Nevertheless, altogether the presented results provide further evidence that, even in healthy anesthetized rodents, the transport of HP Pyr across the BBB is sufficiently fast to permit detection of its metabolic conversion within the brain when using appropriate acquisition protocols. Therefore, we propose that metabolic imaging of HP pyruvate is a viable noninvasive tool for probing rodent brain pyruvate metabolism in preclinical studies.…”
Section: Discussionmentioning
confidence: 61%
“…26 Recent reports on mice suggest that hyperpolarized glucose might show greater response to alterations in cellular energy metabolism, due to it entering the cells via more effective glucose transporters and reporting on actual de novo synthesis of lactate. 45,46 However, experimental use of hyperpolarized glucose is complicated by short T 1 and has so far been successfully demonstrated only in mice.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, unlike the case of the bicarbonate signal, where a CO 2 is released directly because of enzymatic activity and rapidly equilibrated with bicarbonate, the observed lactate signal mainly reflects labelling of the pre‐existing lactate pool, both signals being heavily modulated by pyruvate uptake 26 . Recent reports on mice suggest that hyperpolarized glucose might show greater response to alterations in cellular energy metabolism, due to it entering the cells via more effective glucose transporters and reporting on actual de novo synthesis of lactate 45,46 . However, experimental use of hyperpolarized glucose is complicated by short T 1 and has so far been successfully demonstrated only in mice.…”
Section: Discussionmentioning
confidence: 99%